Lymphoscintigraphy Defines New Lymphatic Pathways from Cutaneous Melanoma Site: Clinical Implications and Surgical Management. (25th December 2011) - Marone, Ugo; Aloj, Luigi; Di Monta, Gianluca; Caracò, Corrado
Abstract : Sentinel lymph node biopsy is commonly applied as staging procedure of regional lymph nodes in patients with cutaneous melanoma. Dynamic lymphoscintigraphy defines the lymphatic pathways from a primary melanoma site and allows to identify the node receiving lymphatic drainage from the primary tumor, which is the sentinel lymph node. In rare cases, lymphoscintigraphy shows sites of lymphatic drainage in nonclassical basins never described in the past when lymphatic drainage was considered only according to the anatomical proximity of the tumor primary site. These peculiar sentinel nodes, so-called "uncommon/interval" nodes, must be surgically removed because they may contain micrometastatic disease and may be the only site of nodal involvement.